2021
DOI: 10.1038/s41467-021-22177-1
|View full text |Cite
|
Sign up to set email alerts
|

Peginterferon Lambda-1a for treatment of outpatients with uncomplicated COVID-19: a randomized placebo-controlled trial

Abstract: Type III interferons have been touted as promising therapeutics in outpatients with coronavirus disease 2019 (COVID-19). We conducted a randomized, single-blind, placebo-controlled trial (NCT04331899) in 120 outpatients with mild to moderate COVID-19 to determine whether a single, 180 mcg subcutaneous dose of Peginterferon Lambda-1a (Lambda) within 72 hours of diagnosis could shorten the duration of viral shedding (primary endpoint) or symptoms (secondary endpoint). In both the 60 patients receiving Lambda and… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
100
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 118 publications
(101 citation statements)
references
References 43 publications
(65 reference statements)
0
100
0
1
Order By: Relevance
“…Mice were intratracheally administered immune complexes composed of purified, polyclonal anti-SARS- bronchoalveolar lavage (BAL) was performed and the collected fluid was promptly analyzed for immune cell and cytokine content. This time point was chosen based on established mouse models of immune complex mediated activities in the lung 12,13 .…”
Section: Neutralizing Antibody Dynamics In a Ten-month Longitudinal Cohort Of Covid-19mentioning
confidence: 99%
See 2 more Smart Citations
“…Mice were intratracheally administered immune complexes composed of purified, polyclonal anti-SARS- bronchoalveolar lavage (BAL) was performed and the collected fluid was promptly analyzed for immune cell and cytokine content. This time point was chosen based on established mouse models of immune complex mediated activities in the lung 12,13 .…”
Section: Neutralizing Antibody Dynamics In a Ten-month Longitudinal Cohort Of Covid-19mentioning
confidence: 99%
“…Longitudinal samples from 109 SARS-CoV-2-infected outpatients were obtained from a phase 2 randomized controlled trial of Peginterferon Lambda-1a (Lambda, NCT04331899). Inclusion/exclusion criteria and the study protocol for the trial have been published 12 . Plasma samples were collected up to 24 hours before first vaccine dose, up to 24 hours before second dose, and 4-8 weeks after second vaccine dose.…”
Section: Stanford Lambda Cohortmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the study was not powered to look at clinical evolution, 5 (16.7%) in the placebo group and 1 (3.3%) in the peg-IFN-λ group required visit to the emergency room by day 14. On the other hand, another study with a similar design showed that peg-IFN-λ did not shorten the duration of viral shedding [ 152 ]. Differences in results between these two studies may be due to differences in baseline viral loads (58% of subjects with >6.0 log copies/ml in the former vs. 75% with <5.5 log copies/ml in the latter) as well as differences in SARS-CoV-2 antibody positivity at baseline (0% in the treatment group and 10% in the placebo group in the former vs. 25% in the treatment group and 46.7% in the placebo group in the latter).…”
Section: Type III Ifn: Ifn-λmentioning
confidence: 99%
“…Some immunotherapies targeted directly to the cytokine storm have been evaluated in COVID-19 patients [129,130]. However, it has been evident that an optimal benefit of anti-cytokine therapies may be plausible if administered during a restricted window of time, at the onset of "cytokine storm" but before sudden disease causes irreparable tissue injury [131,132].…”
Section: Usefulness Of Anti-inflammatory Drugs Administered Upstream Of Hyperinflammationmentioning
confidence: 99%